2016
DOI: 10.1002/jemt.22639
|View full text |Cite
|
Sign up to set email alerts
|

Role of spermatogonial stem cells extract in transdifferentiation of 5-Aza-2′-deoxycytidine-treated bone marrow mesenchymal stem cells into germ-like cells

Abstract: As one of the induced pluripotent stem cells (iPSCs) methods, spermatogonial stem cells (SSCS ) extract is considered as new approach in stem cell therapy of infertility. 5-aza-2'-deoxycytidine (5-aza-dC) inhibits methyltransferase enzyme, and induces gene reprogramming; herein, the effects of SSCS extract incubation in 5-aza-dC-treated bone marrow mesenchymal stem cells (BMMSCs) has been surveyed. BMMSCs were isolated from femurs of three to four weeks old male NMRI mice, and the cells at passage three were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Prepubertal boys present a significant challenge to FP because the only option that can be offered at the moment is cryopreservation of spermatogonial stem cells. 29 This procedure has emerged only in recent years and was not allowed in all participating countries at the time the EBMT survey was carried out; in fact, only 11 centers offered this method as an FP option. Spermatogonial stem cell cryopreservation represents a highly experimental technique and has only been proven to be effective in a mouse model; thus, its acceptance by professionals and parents is low, 30 in line with the low prevalence of its use reported in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…Prepubertal boys present a significant challenge to FP because the only option that can be offered at the moment is cryopreservation of spermatogonial stem cells. 29 This procedure has emerged only in recent years and was not allowed in all participating countries at the time the EBMT survey was carried out; in fact, only 11 centers offered this method as an FP option. Spermatogonial stem cell cryopreservation represents a highly experimental technique and has only been proven to be effective in a mouse model; thus, its acceptance by professionals and parents is low, 30 in line with the low prevalence of its use reported in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…All of the infertility factors in men have not been identified yet and more comprehensive studies are required (1). Approximately, 15% of male infertility is related to genital and urinary tract infectious agents (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…A major obstacle to the reprogramming of somatic stem cells to commit to the cell types from a different germ layer is their epigenetic memory in the form of DNA methylation, limiting the potency of the cells. Previous studies showed that epigenetic modifications with 5-Bromo-2'deoxyuridine (BrdU) [1] or decitabine (5-aza-2'deoxycytidine) [19], increased the potency of MSCs. Decitabine induces DNA demethylation by blocking DNA methyltransferase and prevent differentiation of neural progenitors [20].…”
Section: Introductionmentioning
confidence: 99%